Study of hepato-renal syndrome in patients of cirrhotic ascites in an academic hospital - Siam, Muhammad Masrur; Alam, Shahinul; Fatema-Tuz-Zohora; Khan, M. Morshedul Alam; Alam, M. Shah; Akhter, Nahid (International Journal of Research in Medical Sciences, 2026)
Background: Acute renal impairment is common in patients with chronic liver disease, occurring in approximately one fifth of hospitalized patients with cirrhosis. Considering limited evidence of epidemiological information of this topic, the study was designed to identify the number of patients suffering from hepatorenal syndrome (HRS) among patients of cirrhotic ascites admitted in an academic hospital. Methods: This hospital based cross-sectional type observational study was conducted at the department of medicine and gastroenterology. Total 100 subjects were interviewed. Data were collected by researcher with a structured questionnaire. After the interview the investigator recorded the collected information and later on transcribed into statistical software. Finally, data were analyzed by the SPSS 21. Results: Total 100 subjects were studied and mean age was 46.31±10.75 years, ranging from 22 to 65 years. Majority of the participants were male (69%). The most common cause of cirrhosis of liver was chronic hepatitis B infection (45%), followed in second and third by NAFLD (25%) and chronic hepatitis C (18%). In according to the Child-Turcotte-Pugh class, about 51% were in CP class A, 36% were in class B and remaining 13% were in class C. Overall frequency of HRS was 17% and type 2 was predominant (7%-type 1 HRS vs 10%-type 2 HRS). Conclusions: Less than one fifth of the patients developed HRS and it is associated with higher Child-Pugh class. However, further studies are needed to establish and use the findings.